The moderating impact of good governance on the relationship between Covid-19 knowledge, attitude, compliance and sustainable development goals in Nigeria - Nasiru, Muhammad Anka; Md Dahlan, Nuarrual Hilal (Psychology and Education Journal, 2020)
Not long ago, the Covid-19 epidemic has touched practically every aspect of life in Nigeria, just as it did to most global communities. The disease pandemic triggered Nigeria‟s government to important shutdowns sectors, including education, markets, flight, worship places, recreation facilities, and healthcare services. However, the lockdown intended to limit the Coronavirus spread has made little impact curtailing the disease outbreak. The failure to make progress in the preceding situation might be due to the poor palliative measures adopted to mitigate poverty and misery among the citizenry, occasioned by the non personal movement, poor knowledge among people, negative attitude of the people to the disease, and poor compliance with preventive measures is inimical to national development. More importantly, perhaps the lack of good governance that is persistent in Nigeria might have compounded the problem of realizing sustainable development goals. This study‟s objective was to assess good governance‟s moderating impact on the relationship between knowledge, attitude, compliance, and sustainable development goals (SDGs) in Nigeria. This study used across-sectional survey design, a simple random sampling technique, and a web-based questionnaire and collected 312 functional responses analyzed using SPSS v24 and PLS-SEM. The result of the study focused on the direct and indirect relationship. In the direct hypotheses, the result indicated significant positive relationships between knowledge (β=0.21, t=5.25, p<0.01), attitude (β=0.13, t=3.25, p<0.01), compliance (β=0.60, t=15, p<0.01) and SDGs. In the indirect hypotheses, the result shows that good governance moderated the relationships between knowledge (β=0.17, t=2.09, p<0.01), attitude (β=0.48, t=7.65, p<0.01), compliance (β=0.35, t=8.75, p<0.01), and SDGs. Therefore, the study‟s result indicated that good governance is crucial as it strengthens SDGs‟ attainment in Nigeria. This study recommends that entrenching quality democratic governance in Nigeria should be prioritized by the government, citizenry, international organizations, and donor agencies by ensuring transparency and accountability, the rule of law, and popular participation and consultation fundamental for sustainable development.